Comparative Analysis of Economic Effects of Soft Microgel Flooding and Polymer Flooding. (September 2020) - Ye, Yinzhu; Wu, Xingcai; Liu, Yang; Bo, Xiaosong; Xu, Hanbing; Peng, Huanhuan; Li, Shichao
Abstract: Soft microgel is discontinuous phase. Profile control and flooding technique of soft microgel, deferent from polymer flooding, is a technical method of secondary development of old oil fields. In this paper, we further enrich the flooding mechanism of soft microgel and propose the mechanism of targeting of oil displacement on the basis of synchronous flooding. Profile control and flooding technique of soft microgel has been applied in many oil fields at home and abroad and achieved significant effect of reducing water production and increasing oil. For evaluating the technical and economic effects, firstly, we summarize and analyse the field test results of SMG flooding technology in five oilfield blocks including Huabei oilfield, Changqing oilfield and son on. What's more, the field data of polymer flooding is investigated by consulting scientific papers. At last we compare and analyse the economic effects of soft microgel and polymer flooding by using EOR value and barrel oil cost as evaluation indexes, According to the incomplete statistical data, the economic effect of soft microgel deep flooding technology is better than that of polymer flooding technology.